Concomitant Presence of Ovarian Tumors (Teratoma and Granulosa Cell Tumor), and Pyometra in an English Bulldog Female Dog: A Case Report - Oviedo-Peñata, Carlos A.; Hincapie, Luis; Riaño-Benavides, Carlos; Maldonado-Estrada, Juan G. (Frontiers in Veterinary Science, 2020)
The diagnosis of ovarian tumors in dogs is usually complicated because the clinical signs can be very discrete and can be easily confused with other diseases. There are few reports of ovarian tumors with different cellular characteristics in the same dog. Our objective was to describe an unusual case of the concomitant presence of ovarian teratoma and granulosa cell tumors in a female dog presenting symptoms compatible with pyometra at clinical consultation. Clinical history: A non-spayed six-years-old female English Bulldog was attended at the consultation, with no history of previous steroid hormonal treatment. The dog had presented regular estrus every six months; three months elapsed between the last estrus and consultation. The dog had presented vulvar discharge for more than two weeks. Clinical and laboratory findings: the patient presented a slightly pale oral mucosa, decay, vulvar edema, and mucous-purulent uterine discharge. The ultrasound examination revealed the presence of neoformations in the ovaries, and evidence of cystic endometrial hyperplasia-pyometra in the uterus. Treatment: We performed a ventral ovariohysterectomy. During the surgical procedure, it was found several masses in the left and right ovaries, exhibiting characteristics of other tissues different from ovarian tissue. All samples were sent for histopathological examination. The diagnosis was a granulosa cell tumor in the left ovary and a well-differentiated teratoma in the right ovary. Conclusion: Practitioners must improve the use of diagnostic tools when attending non-spayed dogs at advanced ages (more than six years old), which would probably be at high risk of suffering from undetected ovarian tumors, some of them with malignancy behavior.